Aqueous phase reforming of xylitol and xylose in the presence of formic acid. Issue 15 (14th July 2020) - Alvear, Matias; Aho, Atte; Simakova, Irina L.; Grénman, Henrik; Salmi, Tapio; Murzin, Dmitry Yu.
Abstract : Aqueous phase reforming (APR) of xylose and xylitol was studied over Pt/Pd catalysts in the presence of formic acid simulating an industrial feedstock. Abstract : Aqueous phase reforming (APR) of xylose and xylitol was studied over Pt/Pd catalysts supported on mesoporous carbon (Sibunit) in the temperature range 175–225 °C in a laboratory-scale packed bed reactor. Formic acid was introduced to the reaction mixture to simulate an industrial feedstock from the reactive extraction of hemicelluloses from biomass. The conversion was higher in xylose APR, however, xylitol APR displayed a higher selectivity to hydrogen and stable operation under the conditions investigated. Addition of formic acid increased the hydrogen production in the APR of xylitol, while xylose APR displayed an opposite behavior. The ratio of the gas and liquid products was similar for both substrates at an equal conversion, however, the alkane distribution was different, depending on the presence of formic acid and reaction temperature. It can be concluded that the APR of xylitol to hydrogen was successfully conducted with the selected catalyst in the presence of formic acid as a co-reactant.